Capital controls and international economic law - Mercurio, Bryan (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
"This book explores the tension between capital controls and international economic law. The book will establish whether the IMF has the authority to regulate the use of capital controls and analyse whether a country's use of capital controls is consistent with obligations undertaken in various trade and investment agreements"--
The liberalisation of capital flows -- Capital flow management measures -- Shifting the IMF mandate -- The legality of the IMF's mandate expansion -- The multilateral trade framework -- Bilateral and regional trade agreements -- International investment agreements -- Conclusions.
BIBINDX
Keywords: Capital movements -- Law and legislation